Determinants of breast cancer prevention in a group of women with cancer suspicion - Edyta Kwilosz; Joanna Grzesik-Gąsior; Patrycja Dobrowolska (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Introduction: Due to constant increase incidence of breast cancer in the world, the most important aspect is monitoring of preventive actions and increasing the health awareness of breast cancer in societies, especially in the group of people with high probability of oncological problems. The aim of the study was to analyze selected factors determining women's uptake of breast cancer prevention activities. Material and methods: The study was conducted by diagnostic survey among 121 women, patients of the oncology clinic in Brzozów. Women's knowledge, sociodemographic indicators and positive family history of breast cancer were assessed. Research tool was the proprietary questionnaire. The chi-square (χ2) test was used to verify the hypotheses. A significance level of p < 0.05 was assumed. Results: The most common source of knowledge about breast cancer prevention was the Internet (52.89%), and the main reason for forgoing preventive examinations was lack of awareness of the disease's risks (38.84%). Over 30% of the respondents had a low level of knowledge which was statistically diverse in terms of education (p < 0.001) and respondents age (p = 0.01). Younger and better educated women have a higher level of knowledge, which was related to the regularity of preventive actions (p = 0.048) and breast self-examination (p < 0.001). The occurrence of breast cancer in the family was impact to regulary self-examination and diagnostic tests (p < 0.001). Conclusions: The level of knowledge in the term of breast cancer prevention wasn't satisfactory and need supplementing. The most frequently indicated source of information was Internet what show need to increase the participation of medical specialists in oncology education. The most important predictors of taking regularly preventive actions were young age, higher level of knowledge, higher education and a positive family history (breast cancer).